Implementasi Metode Talaqqi Dalam Proses Pembelajaran Hafalan Al-Qur’an Siswa SD Al-Qur’an Wahdah Islamiyah Polewali - Sudirman, Sudirman; Nurzamsinar, Nurzamsinar; Dewi, Namira; Mardiah, Mardiah; Nurmadia, Sitti; Yusriah, Yusriah (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
The purpose of this research is to find out how the talaqqi method is implemented in the Al-Qur'an memorization learning process for students at Wahdah Islamiyah Polewali Al-Qur'an Elementary School and to find out the supporting and inhibiting factors in implementing the talaqqi method in the Al-Qur memorization learning process. 'an student at SD Al-Qur'an Wahdah Islamiyah Polewali. This type of research is a type of qualitative descriptive research, which is a descriptive analysis of data obtained in the form of words, images or behavior and provides an overview of the conditions studied in the form of a narrative description. The implementation of the talaqqi method in schools is going well with the steps for implementing it, namely: the ustadzah explains, then gives an example of the verse to be memorized with clear articulation and mouth movements, then students imitate the ustadzah's reading. Supporting factors include: Islamic elementary schools, appropriate leaders, qualified teachers, collaboration between teachers, understanding and application of Tajwid rules, mastery of methods, as well as students as objects and their readiness to memorize. Inhibiting factors are teacher indiscipline, less than optimal application of methods, lack of teacher concern for student memorization, student difficulty in pronouncing letters, student indiscipline and less conducive space.